PENGARUH FIRM SIZE TERHADAP HUBUNGAN INTELLECTUAL CAPITAL DENGAN KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan yang Terdaftar di BEI 2001-2010) - Muhammad Al Amin (Optimum: Jurnal Ekonomi dan Pembangunan, 2011)
This study aims to test empirically the influence of firm size and intellectual capital on corporate performance. Intellectual Capital is comprised of (consists of) intellectual materials (knowledge, information, property intellectual capital, experience) that can be used to create wealth. This construct is believed to play an important role in increasing corporate value and financial performance. Based on the sampling method with the method of purposive sampling with the period 2001-2010 study obtained a sample of 17 companies and data obtained as many as 170 data Ganti jadi A purposive sampling technique within period 2001-2010 resulted in sample of 17 companies and 170 data. Hypothesis testing is done using multiple linear regression analysis. The results suggest that intellectual capital has a positive effect on corporate performance, but when diinteraksikan with firm size effect of the variable will be negative. Ganti jadi: Having tested by multiple regression analysis, the findings reveal that intellectual capital has a positive effect on corporate performance. However, this effect turns to be negative when it interacts with firm size.